HYBRID FINANCIAL REPORTS FOR WAQF PROJECTS TOWARDS ENHANCING ACCOUNTABILITY AND TRANSPARENCY OF WAQF INSTITUTIONS IN MALAYSIA: A CONCEPTUAL PAPER - Mohd Syazwan Karim; Sharifah Norhafiza Syed Ibrahim; Nur Farahah Mohd Pauzi; Khairiah Ahmad; Adriana Shamsudin; Azlan Md Thani (Journal of Islamic, Social, Economics and Development, 2022)
Nowadays, the number of waqf projects is on the rise in Malaysia. Several publicuniversities have initiated and managed waqf projects in various sectors, including theagriculture sector. These waqf projects contribute significantly to the economic and socialdevelopment of the country. Despite its increasing popularity and importance, the sustainabilityof waqf institutions may be jeopardized due to its poor accountability and transparency. Thelack of suitable accounting standards and regulation could compromise the quality andcomparability of accounting information. This research aims to propose a set of practical andapplicable hybrid financial report for agriculture waqf projects with income generationprospects. The proposed conceptual model would be a tool that will help transform theconventional reporting into a more transparent financial reporting by integrating theconventional accounting standards and waqf accounting practices from various policy makersto enhance and enrich the good corporate governance practices. Consecutively, it will helppolicy makers in issuing comprehensive financial reporting guideline and framework for waqfinstitutions which ultimately would enhance the confidence level amongst waqf contributors forwaqf funding as instruments for economic and social development